Reiter′s Sundrome With Secondary Amyloidosis - Sayal S.K; Sanghi S; Prasad G.K (Wolters Kluwer Medknow Publications, 2001)
A 35 year old male had arthropathy of large joints, psoriasiform skin lesions and circinate balanitis preceded by recurrent episodes of dysentery. He also developed feature of nephritic syndrome due to secondary amyloidosis as confirmed by renal and rectal biopsy.